let NORM1, NORM2 be Function of ,REAL; :: thesis: ( ( for x being object st x in the_set_of_RealSequences_l^ p holds
NORM1 . x = (Sum (() rto_power p)) to_power (1 / p) ) & ( for x being object st x in the_set_of_RealSequences_l^ p holds
NORM2 . x = (Sum (() rto_power p)) to_power (1 / p) ) implies NORM1 = NORM2 )

assume that
A2: for x being object st x in the_set_of_RealSequences_l^ p holds
NORM1 . x = (Sum (() rto_power p)) to_power (1 / p) and
A3: for x being object st x in the_set_of_RealSequences_l^ p holds
NORM2 . x = (Sum (() rto_power p)) to_power (1 / p) ; :: thesis: NORM1 = NORM2
A4: for z being object st z in the_set_of_RealSequences_l^ p holds
NORM1 . z = NORM2 . z
proof
let z be object ; :: thesis: ( z in the_set_of_RealSequences_l^ p implies NORM1 . z = NORM2 . z )
assume A5: z in the_set_of_RealSequences_l^ p ; :: thesis: NORM1 . z = NORM2 . z
NORM1 . z = (Sum (() rto_power p)) to_power (1 / p) by A2, A5;
hence NORM1 . z = NORM2 . z by A3, A5; :: thesis: verum
end;
A6: dom NORM2 = the_set_of_RealSequences_l^ p by FUNCT_2:def 1;
dom NORM1 = the_set_of_RealSequences_l^ p by FUNCT_2:def 1;
hence NORM1 = NORM2 by ; :: thesis: verum